THE EUROPEAN UNION, CHINA AND SOLAR PANEL - Adieuva Innocenthia; Yosinta Margaretha; Febri One; Junita Christine; Agnes Magdalena (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
The European Union and China are the two countries that have advantages in each of them. The European Union and China have a dispute regarding renewable energies, namely the problem with solar panels. China's policy of making solar panels prices have low bargaining power makes the European Union unable to accept the policy because it can cause a long trade conflict. The case study in this paper also illustrates that the EU is actively approaching it to overcome environmental challenges in China by involving the European Union in dialogue and negotiation on various issues and providing capacity-building support. China also introduced trade reforms and carbon emissions to environmental decision-making bodies in the European Union, and it was supported by the European Union, including through meetings to determine sustainable policies and development projects on energy and the environment. Keywords: EU – China dispute, Environmental Challenges, anti-dumping, China’s policy, World Trade Organization.